REVERSE RADIAL ARTERY FLAP FOR SOFT TISSUE DEFECTS OF HAND IN PEDIATRIC AGE GROUP - Cheema, Saeed Ashraf; Talaat, Nabeela (Journal of Ayub Medical College Abbottabad, 2009)
Background: To highlight the usefulness of reverse radial artery flap in covering various soft tissue defects of hand in paediatric age group. Methods: A total of 16 reverse radial artery flaps were utilized in a period of three years to cover various soft tissue defects of hand for paediatric age group patients. The age ranged from 5-18 years. The two common causes of soft tissue defects in this series were mechanical trauma and fireworks trauma with five cases in each group. Three of the cases were burn victims and other two presented with earth quake injuries. One patient had wound because of road traffic accident. Soft tissue defects of palm were covered with this flap in eight cases while in three cases it was wrapped around the thumb. First web space defects were covered with this flap in two cases. Two cases required coverage of amputation stump at transmetacarpal level and yet another required a big flap to cover the soft tissue defects at palm, dorsum and thumb. Donor site was covered with split skin graft in all cases but one, which was closed primarily. Results: We had partial loss of flap in one case. Grafted donor sites healed uneventfully and were quite acceptable to the patients in due course of time. Conclusion: Reverse radial artery flap has a quite long arc of rotation which brings it great ease to cover the soft tissue defects of various areas of hand like palm, dorsum, first web space and thumb. Keywords: Reverse radial artery flap, Hand injuries, Paediatric hand trauma